PERAN PENGAWAS DALAM MENINGKATKAN KOMPETENSI KEPALA MADRASAH DI KABUPATEN MAJALENGKA - Siti Evi Alivia (Pascasarjana Unviersitas Majalengka, 2021)
The research was motivated by the phenomenon of the low competence of madrasah principals, aiming to determine the efforts of madrasa supervisors in improving the competence of madrasah principals. The research uses an approach, data collection tools use interviews and observations. Informants were selected purposively, consisting of supervisors, madrasa heads, teachers, and madrasa committee administrators. The data were analyzed descriptively qualitatively with a pedagogical and psychological approach through data reduction, data presentation, and conclusion drawing. The results of the study indicate that: a) Supervision is carried out by supervisors through coaching, training, and supervision activities, either directly or indirectly; b) The managerial supervision method uses observation, evaluation, reflection, and FGD; c) The results of supervision in improving the competence of madrasah principals in the form of increasing insight, knowledge, and work motivation of madrasah principals and educators; d) In managing madrasah, the head implements managerial functions, organizes madrasa administration, creates a conducive work climate, and strives to meet eight national education standards; e) Two inhibiting factors were found, namely internal and external factors.